Values and storytelling in the fashion films. The case Tender Stories (2014-2017), by Tous. - Méndiz Noguero, Alfonso (2018)
Communication of fashion brands shapes their identity according to the corporate values shown in their advertising. The current tendency of storytelling highlights the significance of immaterial aspects, since narrative campaigns promote values rather than products and offer stories rather than arguments. With the emergence of fashion films, fashion brands have turned to emotional and narrative communication: while products remain in the background, values and storytelling become the backbone of the discourse.In this study, we will analyze the series of fashion films Tender Stories (2014-2017), from the jewelry firm Tous, whose stories focus on the concept of love. For this, we will use the film analysis proposed by García-Noblejas ("first and second navigations") to discover how Tous conceives love in various relationships (courtship, marriage, parent-child relationship) and how the brand conceives it as a corporate value within its storytelling